Designación de los representantes de las comunidades negras, para la efectividad de la consulta previa (2017)
Although it is true that prior consultation is a fundamental right protected, and supported in OIT Convention of 169, which does not establish rules against the election of representatives of black communities and violations of the law, That leave the process depends only on the principle of good faith; The State requires an institutional adaptation in which it can respond satisfactorily to the dynamics of that fundamental right; Especially to solve assertively questions that today concentrate the attention of experts, government, guilds, and so evaluate, re-evaluate and reinvent procedures, in order to curb vices, and ensure full exercise and enjoyment of rights, that is why Propose the actions to be undertaken, to achieve legitimacy in the delegation of representatives of the black communities for prior consultation, based on the systemic case analysis.